ASSESSING PERCEPTIONS OF THE SAUDI POPULATION REGARDING DISASTER PREPAREDNESS (CAHIERS MAGELLANES-NS, 2024)
Background:  Disaster preparedness consists of a set of measures undertaken in advance by governments, organisations, communities, or individuals to better respond and cope with the immediate aftermath of a disaster, risk perception entails the awareness, beliefs, and attitudes concerning the likelihood, severity, threat intrusiveness, and additional attitudinal factors that may reflect on the manner in which one perceives the risk posed by any given threat Objectives: To assess perceptions of Saudi populations regarding disaster preparedness.Methods: Descriptive community-based survey. samples were taken from all its regions of Kingdom of Saudi Arabia, 561 Samples were collected from adults over the age of 18, between Janoury and April 2023.The information was gathered by standardized, close-ended Questionnaire. Before data collection, the study had received approval from the Al-Taif University ethical committee.Results: Most of the participants are between the ages of 29-49 (68.1%) and There is a statistical association between age and the perception of disasters preparedness PV (.001). 67% of the participants are men and they are more perception of disasters preparedness than women PV (.003)، More than half of the study sample are university educated. There is no a statistical association between the level of education and perception of disasters preparedness PV (.122).Conclusion: The participants had average awareness and knowledge about disaster preparedness, how they occur and prevented, and what role they play in making a decision when disasters occur. We recommended to add and create educational programs to raise awareness, making sure that they are also integrated into education at the local and international levels and more recherché need.